Pendampingan Program Rumah Bibit Sebagai Upaya Mewujudkan Ketahanan Pangan Lembang Sa’dan Ulusalu, Toraja Utara - Vonnisye Marthinus; Berlian Zetikarya Haryati; Dwi Prasetyawati Thana; Adewidar Marano Pata'dungan; Ernytha Galla; Willy Yavet Tandirerung; Jens Batara Marewa (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
The neighborhood benefits greatly from the nursery program. The established program seeks to educate the general public about the construction and use of seedling houses. The seed bank offers the community assistance in preparing the vegetable seeds that are required by the community. implementation of the service program starting on July 12, 2022, for one month. Through observational methods, interviews, demonstrations, empowerment activities (counseling, training, mentoring, and building seedling houses), and assessment, data were gathered. The population of Lembang Sa'dan Ulusalu, Sa'dan District, and North Toraja Regency is the program's target audience. The extension of the seedling house program and nursery techniques to the community constitutes the first stage of empowerment activities. The second stage involves instruction and support in the production of growth regulators and organic fertilizers; the third involves the building of seed houses; and the fourth involves nursery support. The community is very passionate and supportive of this activity, as indicated by the improvement in community knowledge and abilities. They are also getting ready to start nursery activities regularly again.Keywords: Mentoring; nursery program; knowledge; abilities